2022
DOI: 10.1097/01.gox.0000828852.36524.3d
|View full text |Cite
|
Sign up to set email alerts
|

P126. A Comparison of the Clinical Wound Healing Outcomes of Autologous Skin Grafts and Tissue-Engineered Skin Constructs: A Systematic Review and Meta-Analysis

Abstract: PRS Global Open • 2022 flaps. 30-day mortality following reconstruction was 3.9%. Median length-of-stay after initial debridement was 8 days (IQR5-15). Of patients with flaps, 54 (48%) required multiple debridements prior to closure, and 30 (27%) underwent reoperation after flap closure. Patients who needed only a single debridement were significantly less likely to have a complication requiring reoperation (N= 10/58 vs 20/54, 17% vs 37%, p=0.02), undergo a second flap (N=6/58 vs 17/54, 10% vs 32%, p<0.001) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies have shown that skin transplantation has a significant improvement in the treatment of diabetic wounds. [10][11][12] Skin transplantation can be divided into homotransplantation and xenotransplantation according to the source of substitutes. Autologous transplantation needs to create new wounds in different parts of the patient's own body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that skin transplantation has a significant improvement in the treatment of diabetic wounds. [10][11][12] Skin transplantation can be divided into homotransplantation and xenotransplantation according to the source of substitutes. Autologous transplantation needs to create new wounds in different parts of the patient's own body.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, collagen dressings and silver sulfadiazine cream commonly used in clinical practice need to be replaced frequently, which is likely to cause secondary damage to the wound surface of patients and cause some trouble to health care providers 9 (Figure 1). Many studies have shown that skin transplantation has a significant improvement in the treatment of diabetic wounds 10–12 . Skin transplantation can be divided into homotransplantation and xenotransplantation according to the source of substitutes.…”
Section: Introductionmentioning
confidence: 99%